DEFORMATION ROUGHNESS UNDER CYCLIC AND STATIC LOADS - Karuskevich, О.М.; Maslak, Т.P.; Hui, Zhang Zhao (Proceedings of National Aviation University (archive), 2005)
The experiments are aimed to develop a new non-destructive method for fatigue damage diagnostics. This method is based on monitoring deformation roughness which is formed on the surface of aluminum structural alloys. The evolution of this roughness near the stress concentrator has been monitored at various stages of fatigue life under the stress level close to the operational stress level on the fuselage skin of modern aircraft. The deformation relief under static loads is represented as well.